Laparoscopic versus open liver resection for colorectal liver metastasis: an umbrella review - Pinto, Federico; Pangrazio, Marco Di; Martinino, Alessandro; Todeschini, Letizia; Toti, Francesco; Cristin, Luca; Caimano, Miriam; Mattia, Amelia; Bianco, Giuseppe; Spoletini, Gabriele; Giovinazzo, Francesco (Frontiers in Oncology, 2024)
This study comprehensively compared laparoscopic liver resection (LLR) to open liver resection (OLR) in treating colorectal cancer liver metastasis (CRLM). We assessed a range of critical surgical and oncological outcomes through a systematic review of relevant literature. Our findings revealed that minimally invasive surgery (MIS) did not significantly prolong operative time compared to open liver resection and notably demonstrated lower blood transfusion rates and reduced intraoperative blood loss.While some studies favoured MIS for its lower complication rates, others did not establish a statistically significant difference. One study identified a lower post-operative mortality rate in the MIS group.Furthermore, MIS consistently correlated with shorter hospital stays, indicative of expedited postoperative recovery. Concerning oncological outcomes, while certain meta-analyses reported a lower rate of cancer recurrence in the MIS group, others found no significant disparity. Overall survival and disease-free survival remained comparable between the MIS and open liver resection groups. Our analysis highlights the potential advantages of LLR in terms of surgical outcomes and aligns with existing literature findings in this field.